Dihydroartemisinin–piperaquine resistance in Plasmodium falciparum malaria in Cambodia: a multisite prospective cohort study - Amaratunga, C; Lim, P; Suon, S; Sreng, S; Mao, S; Sopha, C; Sam, B; Dek, D; Try, V; Amato, R; Blessborn, D; Song, L; et al. (Elsevier, 2016)
Background Artemisinin resistance in Plasmodium falciparum threatens to reduce the efficacy of artemisinin combination therapies (ACTs), thus compromising global efforts to eliminate malaria. Recent treatment failures with dihydroartemisinin-piperaquine, the current first-line ACT in Cambodia, suggest that piperaquine resistance may be emerging in this country. We explored the relation between artemisinin resistance and dihydroartemisinin–piperaquine failures, and sought to confirm the presence of piperaquine-resistant P falciparum infections in Cambodia.